ANALISIS ARUS KAS SEBAGAI SUMBER INFORMASI KAS OPERASIONAL PADA PT JALAN TOL SEKSI EMPAT MAKASSAR - Ester Tamallo (AkMen JURNAL ILMIAH, 2018)
The purpose of this research is to know the information of positive operational source at PT. JalanTol Seeksi EmpatMakassar. The methods used are Direct Methods and Indirect Methods. Direct Methods convert each post to the income statement directly to the cash market, and report all receipts and operations payments. Indirect Method Indirect method reconciles reported earnings with cash flow. Indirect method starts from net income as a cash flow. While the results of research in the preparation of cash flow statement using Direct Method and Indirect Method at PT. The Four Section of Makassar Toll Road can be summarized as follows: Cash and Cash Equivalents in 2015 is decreased because, interest income on deposits, accrued expense sources, bank loans, decrease and purchase of fixed assets and the addition of intangible assets. Cash Flows from PT. . Toll Road Section Four Makassar each year is stated positive in generating cash.So PT. Section Four Toll Road Makassar can maintain, maintain the operating capability of the entity and pay debts, interest, without the help of external funding sources.